2002
DOI: 10.1121/1.1459463
|View full text |Cite
|
Sign up to set email alerts
|

Wheel/rail noise generation due to nonlinear effects and parametric excitation

Abstract: Two models are developed, one in the time domain and another in the frequency domain, to explain when a wheel/rail noise generation model requires the inclusion of discrete supports, parametric excitation, and the nonlinear contact spring. Numerical simulations indicate the inclusion of discrete supports to describe low frequency response, and also at higher frequencies, especially where the rail is very smooth or has a corrugation/wavelength corresponding to the pinned-pinned frequency. With a corrugation, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 5 publications
(1 reference statement)
1
42
0
2
Order By: Relevance
“…They found that non-linearities in the contact model cannot be neglected in the cases of severe roughness and/or a low static contact preload, which can cause loss of contact between wheel and rail. These results have been confirmed by Nordborg [69], who used both a frequency-domain model and a time-domain model based on Green's functions to study non-linear effects in the vertical interaction. If the response to discrete irregularities such as wheel flats and rail joints is to be calculated, time-domain models are the only option.…”
Section: Transient Contact Conditions During Squealsupporting
confidence: 63%
See 2 more Smart Citations
“…They found that non-linearities in the contact model cannot be neglected in the cases of severe roughness and/or a low static contact preload, which can cause loss of contact between wheel and rail. These results have been confirmed by Nordborg [69], who used both a frequency-domain model and a time-domain model based on Green's functions to study non-linear effects in the vertical interaction. If the response to discrete irregularities such as wheel flats and rail joints is to be calculated, time-domain models are the only option.…”
Section: Transient Contact Conditions During Squealsupporting
confidence: 63%
“…This approach is computationally efficient and allows including discrete supports. This technique, going back to Manfred Heckl's proposal for a railway simulation program [136], has been used by Nordborg [69] and recently by Mazilu [26]. As a matter of course, the wheel can also be represented by Green's functions.…”
Section: Time-domain Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…1.2 Theory of the model 1.2.1 Rail Green's function in the frequency domain Green's function, , in the frequency domain for a periodically supported rail is derived in detail in [8,9,10,11]. This is needed to determine the interactive contact force of the rail/wheel and the vibration levels and the radiated noise levels of the rail.…”
Section: Rolling Noise Modelmentioning
confidence: 99%
“…It can be calculated, according to section 1.2.4, in the time-domain with the rail/wheel simulation program [11], and the nonlinear state-dependent rolling contact model [12].…”
Section: Rail/wheel Contact Force Excitationmentioning
confidence: 99%